A Prediction of Laser Beam-to-Cutting Tool in Laser Assisted Micro Milling of Hardened Steel - Ibrahim, Mohd. Rasidi; Mohid, Zazuli; Abd Rahim, Erween; Md. Warap, Norazlan; Ismail, Mohd. Idris Shah (9th International Conference on MicroManufacturing (ICOMM 2014), 2014)
Laser assisted micro milling (LAMM) is one of the methods that used to enhance the ability to manufacture the micro scale product. Laser is used to preheat the workpiece materials prior the machining process. Therefore,reducing the workpiece strength caused by the laser heating need to be controlled to avoid the melting and changing of materials properties. Determining the processing parameters and their effects to the processing characteristics, temperature measurement and the laser spot-to-cutting tool distance are crucially important. In this study, the finite element analysis using ANSYS software was used to predict the heat distribution to characterize the melting and heat affected zone formation. From the results, the estimations of laser spot-to-cutting tool distance together with the allowable depth of cut were determined and applied in the actual LAMM experiment. Meanwhile, the analyses of cutting force and tool wear as an evidence conjunction to the laser heating is applicable to reduce the materials strength was performed.
Keywords: Laser Assisted Micro Milling; Finite Element Analysis; ND:YAG Laser